Dietary intake of DHA during pregnancy: a significant gap between the actual intake and current nutritional recommendations - Regina Wierzejska; Mirosław Jarosz; Barbara Wojda; Magdalena Siuba-Strzelińska (National Institute of Public Health - National Institute of Hygiene, 2018)
Background: Docosahexaenoic acid (DHA) is indispensable to ensure proper development of the fetal central nervous system and pregnancy duration. Daily intake of DHA should be at least 100 mg higher as compared to the pre-pregnancy values. Objectives: The aim of the study was to evaluate DHA intake during pregnancy and compare it to the current recommendations. Material and methods: A total of 100 pregnant women presenting for labor at the Department of Obstetrics, Gynecology and Oncology, Medical University of Warsaw, were included in the study. DHA intake from the following sources: fish and eggs, and DHA preparations collected based on the questionnaire was investigated. Results: Low dietary DHA intake (median: 60 mg/day) was observed. The values were only slightly higher (median: 90 mg/day) after DHA preparations were taken into consideration because only 28% of the pregnant women used DHA preparations. Overall, 92% of the subjects consumed <200 mg of DHA a day, which was the result of insufficient fish consumption (mean: 15 g/day). Only 10% of the respondents ate fish twice a week, in which case the DHA dietary intake was statistically significantly higher (median: 160 mg/day) (p=0.0232). Total median dietary DHA and EPA intake in the study population was 79 mg/day. Conclusions: The diet of pregnant women is largely deficient as far as DHA intake is concerned. Importantly, it is not possible to comply with current recommendations without dietary supplementation.